Research on the Feasibility of Original Theory and System Practice of Child- Computer Interactive Emotion Detecting and Counseling System - Wei, Whei-Jane; Lee, Lai-Chun (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
AI in emotion detection system is a non-intrusive human-machine interaction. The purposes of this study are to develop 40 Sandwich-Dialogue Approach (SDA) animations and to verify its impacts on emotion reaction. The underlying theoretical foundation of SDA is that speaking tone, attitude and rhetoric cause others’ emotion response and accordingly result interpersonal problems. SDA comprises empathy, strengths finding, discussion possible solutions and its impacts on emotion. It is crucial to foster children possessing SDA for a harmonious interpersonal relationship, a positive self-concept, life-long happiness and life-span achievements because early childhood is the critical period of preparing habits, attitudes and characters. This study develops an innovative “Sandwich-Dialogue-Based Emotional Development Theory” with concentration on adults enhancing SDA rather than scolding child’s emotional responses. This is a direct study that child’s emotion is directly detected by Emotional Detection System, so does the SDA. To achieve the goals, the researcher develops 40 SDA animations based on Emotional Competency Rating Scale forYoung Children. There are 196 parents/teachers participated in the SDA training and moreover Emotional Detection System directly detected 189 children’s emotions. These data were collected by the operational platform designed by this study and were automatically calculated by t-test and reliability analysis on Emotional Detection System and SDA. The main findings are that (a) the children’semotional ability scores have improved significantly relying on thetreatment of “Sandwich-Dialogue-Based Emotional DevelopmentTheory” (p <.001); (b) the reliability is .987 for Emotional DetectionSystem and .973 for SDA. “Sandwich-Dialogue-Based Emotional Development Theory” enhance adults’ SDA and accordinglychildren improve their emotions. “Sandwich-Dialogue-BasedEmotional Development Theory” contributes to an innovative emotional development theory that the way how adults stimulate children causes the way how children react to emotions.